2014
DOI: 10.1098/rspb.2013.2792
|View full text |Cite
|
Sign up to set email alerts
|

Endocranial morphology of PalaeocenePlesiadapis tricuspidensand evolution of the early primate brain

Abstract: Expansion of the brain is a key feature of primate evolution. The fossil record, although incomplete, allows a partial reconstruction of changes in primate brain size and morphology through time. Palaeogene plesiadapoids, closest relatives of Euprimates (or crown-group primates), are crucial for understanding early evolution of the primate brain. However, brain morphology of this group remains poorly documented, and major questions remain regarding the initial phase of euprimate brain evolution. Micro-CT inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 34 publications
3
67
0
1
Order By: Relevance
“…; Orliac et al. ; see exceptions in Table S15). The callosciurin R. laticaudatus (USNM 488511) is the only extant sciurid from our sample with a well‐defined sylvian sulcus, a somewhat surprising observation as this feature has often been considered a distinctive trait of Euprimates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Orliac et al. ; see exceptions in Table S15). The callosciurin R. laticaudatus (USNM 488511) is the only extant sciurid from our sample with a well‐defined sylvian sulcus, a somewhat surprising observation as this feature has often been considered a distinctive trait of Euprimates.…”
Section: Discussionmentioning
confidence: 97%
“…; Orliac et al. ; Ramdarshan & Orliac, ; Bertrand & Silcox, ). Consequently, it is becoming possible to better understand crucial aspects related to brain evolution in the two groups, and to look for instances of parallelism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, following Orliac et al . (), the superior sagittal sinus was excluded from the surface area (NS2). Third, we followed Jerison () and Long et al .…”
Section: Methodsmentioning
confidence: 99%
“…While preservation is not adequate to reconstruct the endocast more caudally, it is clear that D. szalayi would have had relatively large olfactory bulbs similar to those reconstructed for other plesiadapiforms including Plesiadapis (Gingerich and Gunnell, 2005;Orliac et al, 2014), Ignacius (Silcox et al, 2009), andMicrosyops (Silcox et al, 2010a). The position of the frontal relative to the maxilla is difficult to reconstruct because of distortion of the specimen, but the front of the olfactory bulbs is clearly fairly far forward, at the level of the orbit as in Ignacius, but not Microsyops or Plesiadapis, in which the endocast extends less far rostrally (Silcox et al, 2009(Silcox et al, , 2010aOrliac et al, 2014). It has been suggested that the apparently more rostral extension of the olfactory bulbs shared between I. graybullianus, dermopterans, and short-faced euprimates might be related to shortening of the face and occurred multiple times in euarchontan evolution (Silcox et al, 2010a).…”
Section: Face and Braincasementioning
confidence: 96%